Socio-Economic Impacts Of Land Function Transfer Of Rice Commodities To Corn Commodities In Nanjungan Village - Rasoki, Timbul; Nurmalia, Ana (Journal of Agri Socio Economics and Business, 2023)
Agriculture is a vital sector in the Indonesian economy, especially in rural areas such as Nanjungan Village. Nanjungan Village faces significant challenges regarding the supply of water for agricultural irrigation. The decreasing water discharge has affected the ability to maintain optimal rice production, thus encouraging farmers to look for alternatives in managing their land with land conversion. This is what causes researchers to be motivated to know the socio-economic impacts resulting from land conversion. The method of determining this sample uses (Simple Random Sampling) or a simple random sample. The population is 358 farmers. According to Arikunto 10% - 15% so that the total sample taken was 15 percent of the total corn farmers in Nanjungan village, namely 54 farmers. This research combines quantitative descriptive research methods. The results of the study stated that the social impacts that occurred were the life cycle of the community, such as the planting and harvesting periods, as well as the reduced work rhythm of farmers after converting their land to corn, so that gathering activities for farmers also decreased. The economic impact that occurs is the income of farmers before land conversion, which is Rp. 21,029,148, - and there is an increase in income after land conversion, namely Rp. 31.102.014,-. The difference in income before and after land conversion is IDR 10,072,866..